Resistome Mapping in Foodborne Pathogens: Understanding Role in the Transmission Dynamics of Resistance Genes - Muneer Oladipupo Yaqub; Chinedu Eucharia Joseph; Aashika Jain; Lekshmi K. Edison (Applied Microbiology)
The emergence of antimicrobial resistance (AMR) in pathogens transmitted through food poses a significant threat to global public health, complicating infection treatment and increasing mortality rates. This review explores the role of resistome mapping as a crucial tool for understanding the transmission dynamics of antimicrobial resistance genes (ARGs) in foodborne pathogens, such as Salmonella, Escherichia coli, Listeria monocytogenes, and Campylobacter spp., as well as various techniques for resistome mapping, such as metagenomic sequencing, PCR-based methods, and whole-genome sequencing (WGS), highlighting the significance of horizontal gene transfer (HGT) as a key mechanism for ARG dissemination in foodborne pathogens. Additionally, we investigated the influence of agricultural practices and environmental factors on AMR development, highlighting the critical need for improved surveillance, antibiotic stewardship, and global collaboration to mitigate the spread of resistant ARGs through the food chain. The perceptions gained from resistome mapping play an essential role in developing effective approaches to address AMR and to ensure food safety.